2021
DOI: 10.1183/13993003.03914-2020
|View full text |Cite
|
Sign up to set email alerts
|

Arterial vascular volume changes with haemodynamics in schistosomiasis-associated pulmonary arterial hypertension

Abstract: Schistosomiasis is a prevalent cause of pulmonary arterial hypertension (PAH), currently classified as group 1 pulmonary hypertension (PH) [1]. In comparison to other aetiologies of PAH, such as idiopathic PAH, schistosomiasis-associated PAH (Sch-PAH) has not been extensively studied. Potential mechanisms of PAH development in schistosomiasis include systemic and localised lung inflammation, involvement of other organs, such as the liver and spleen, and direct blockage of precapillary vessels from parasite egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…One of the manifestations of schistosomiasis is schistosomiasis-induced pulmonary arterial hypertension (SchPAH) [34]. SchPAH is considered a global disease due to the high prevalence of schistosomiasis [35][36][37], with a prevalence of 5% among those chronically infected with schistosomes [38] and 5-30% in patients with hepatosplenic schistosomiasis secondary to Schistosoma mansoni [39][40][41]. Another study showed that SchPAH results in 30.8% of all cases of pulmonary hypertension in endemic areas [42].…”
Section: Pulmonary Schistosomiasismentioning
confidence: 99%
“…One of the manifestations of schistosomiasis is schistosomiasis-induced pulmonary arterial hypertension (SchPAH) [34]. SchPAH is considered a global disease due to the high prevalence of schistosomiasis [35][36][37], with a prevalence of 5% among those chronically infected with schistosomes [38] and 5-30% in patients with hepatosplenic schistosomiasis secondary to Schistosoma mansoni [39][40][41]. Another study showed that SchPAH results in 30.8% of all cases of pulmonary hypertension in endemic areas [42].…”
Section: Pulmonary Schistosomiasismentioning
confidence: 99%
“…Dia mundial da hipertensão pulmonar: reflexões e planejamentos a pesquisa brasileira caracterizou essa forma de HAP do ponto de vista clínico-funcional, hemodinâmico, radiológico e epidemiológico. (3)(4)(5)(6)(7) Foram surgindo no país grupos com expertises distintas, se dedicando a áreas mais específicas do conhecimento das doenças da circulação pulmonar e criando um ambiente muito propício à colaboração.…”
Section: Editorialunclassified